2013
DOI: 10.1021/jm4002583
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Kinetic, and Pharmacodynamic Mechanisms of d-Amino Acid Oxidase Inhibition by Small Molecules

Abstract: We characterized the mechanism and pharmacodynamics of five structurally distinct inhibitors of d-amino acid oxidase. All inhibitors bound the oxidized form of human enzyme with affinity slightly higher than that of benzoate (Kd ≈ 2-4 μM). Stopped-flow experiments showed that pyrrole-based inhibitors possessed high affinity (Kd ≈ 100-200 nM) and slow release kinetics (k < 0.01 s(-1)) in the presence of substrate, while inhibitors with pendent aromatic groups altered conformations of the active site lid, as evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Although the production of branched-chain D-amino acids remains unknown in R. xylanophilus, the substrate specificity indicates the possibility that RxDAO might be involved in the functions of branched-chain D-amino acids through their degradation. In pkDAO, a flexible loop near the active site, called the active-site lid that opens and closes for substrate entry and product exit, is involved in substrate specificity (33,34). In particular, the flexibility of Y224 in the lid is likely important for its broad substrate specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the production of branched-chain D-amino acids remains unknown in R. xylanophilus, the substrate specificity indicates the possibility that RxDAO might be involved in the functions of branched-chain D-amino acids through their degradation. In pkDAO, a flexible loop near the active site, called the active-site lid that opens and closes for substrate entry and product exit, is involved in substrate specificity (33,34). In particular, the flexibility of Y224 in the lid is likely important for its broad substrate specificity.…”
Section: Discussionmentioning
confidence: 99%
“…This link between D -serine and NMDAR function suggested that, by controlling D -serine brain levels, DAAO and serine racemase, the D -serine-synthesizing enzyme [11], are also involved in regulating the key brain functions. Despite the apparent low levels of DAAO in forebrain regions [12], pharmacological studies with DAAO inhibitors [13,14], genetic studies in DAAO knockout animals [15,16] and genetic studies with serine racemase-mutated mice [17,18] have all clearly indicated that D -serine regulatory enzymes impact NMDAR function, synaptic function and cognitive ability. Furthermore, chemical regulators of D -serine metabolism could be effective disease treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chemical regulators of D -serine metabolism could be effective disease treatments. More specifically, as NMDAR hypofunction is a core pathway deficit in schizophrenia [19,20], DAAO inhibitors, perhaps in combination with D -serine systemic administration [21], have the potential to be effective treatments of schizophrenia via their capacity to increase D -serine in the brain and enhance NMDAR-dependent functions [13,14,22]. Moreover, although the mechanistic underpinnings of DAAO's roles in nociception are not fully understood, DAAO inhibitors have been shown to reduce pain in various rodent models of neuropathic pain [23–25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 2-Substituted 6-hydroxy-1,2,4-triazine-3,5(2 H ,4 H )-diones such as 3 exhibited not only potent DAAO inhibitory activity but also improved metabolic stability compared to 1–2 in liver microsomes. 7 This secondary binding site was also exploited by carboxylate-based DAAO inhibitors such as 4 8 and 5 . 9 In the search for a new class of DAAO inhibitors, we have examined a variety of scaffolds that may serve as a bioisostere for the carboxylic acid moiety interacting with the active site of DAAO.…”
mentioning
confidence: 99%